Drivers of growth in the travel and tourism industry in Malaysia: A Geweke causality analysis - Tan Khee Giap; Sasidaran Gopalan; Ye Ye (Economies, 2016)
The travel and tourism industry has been growing in importance for several developing countries. It has not only generated considerable foreign exchange revenues but has also contributed to the overall output and socio-economic development of these countries. Within the Asia and Pacific region, data for 2014 indicates that Malaysia was ranked very highly at no. 26 out of the 184 countries in the world in terms of the relative importance of the contribution of the travel and tourism industry to its national output. In this light, this paper aims to undertake an empirical examination of the factors driving international tourist arrivals into Malaysia. The paper attempts to identify the causal determinants of the growth of the travel and tourism industry, using quarterly data from 2000 to 2012, under a Geweke causality framework. The empirical results suggest Malaysia's government expenditures on tourism promotion as well as infrastructure investments such as enhancing airport facilities are causal and significant determinants of growth in the travel and tourism industry.
Keywords: E2; O40; Z3; 330; Geweke causality; economic growth; travel and tourism; Malaysia; competitiveness